Mars Science Laboratory Observations of the 2018/Mars Year 34 Global Dust Storm. Issue 1 (5th January 2019) - Guzewich, Scott D.; Lemmon, M.; Smith, C. L.; Martínez, G.; de Vicente‐Retortillo, Á.; Newman, C. E.; Baker, M.; Campbell, C.; Cooper, B.; Gómez‐Elvira, J.; Harri, A.‐M.; Hassler, D.; et al.
Abstract: Mars Science Laboratory Curiosity rover observations of the 2018/Mars year 34 global/planet‐encircling dust storm represent the first in situ measurements of a global dust storm with dedicated meteorological sensors since the Viking Landers. The Mars Science Laboratory team planned and executed a science campaign lasting approximately 100 Martian sols to study the storm involving an enhanced cadence of environmental monitoring using the rover's meteorological sensors, cameras, and spectrometers. Mast Camera 880‐nm optical depth reached 8.5, and Rover Environmental Monitoring Station measurements indicated a 97% reduction in incident total ultraviolet solar radiation at the surface, 30K reduction in diurnal range of air temperature, and an increase in the semidiurnal pressure tide amplitude to 40 Pa. No active dust‐lifting sites were detected within Gale Crater, and global and local atmospheric dynamics were drastically altered during the storm. This work presents an overview of the mission's storm observations and initial results. Plain Language Summary: The 2018 Mars global dust storm was observed by six spacecraft in orbit and two rovers on the surface. This paper provides an overview and description of the Mars Science Laboratory Curiosity rover's observations during the storm. For approximately 100 Martian days (sols), the rover conducted an enhanced cadence of environmental observations to study the storm. These are the first observations of a Martian global dust storm with meteorological sensors near the equator. Atmospheric opacity reached a peak of 8.5, attenuating 97% of the total solar ultraviolet radiation at the surface. Most of the dust was sourced from outside Gale Crater, with no indications of dust lifting within the crater during the height of the storm. Meteorological conditions were substantially altered, with changes to the pressure, temperature, and humidity patterns. Dust devil activity ceased for several weeks due to the reduction in temperature contrast between the surface and atmosphere. There was no indication of unusual aeolian transport, suggesting Martian global dust storms are not a major cause of sand dune movement. Key Points: The Curiosity rover conducted a dedicated science campaign to study the 2018 Mars global dust storm Atmospheric opacity reached a peak of 8.5, and horizontal visibility dropped to 2.7 km Meteorological conditions in Gale Crater were substantially altered, with changes to the pressure, temperature, and humidity cycles